Rural marginalisation and multifunctional land use in Finland - Vihinen, Hilkka; Tapio-Biström, Marja-Liisa; Voutilainen, Olli (MTT, 2005)
Suomen maatilat jakautuvat valitun kehitystien perusteella selkeisiin luokkiin. Kolmasosa tiloista kehittää intensiivisesti maatilatalouttaan investoimalla ja laajentamalla tuotantoaan. Toisella kolmanneksella, monialaisilla tiloilla, on maatilatalouden ohella muuta, kotitalouden toimeentulon kannalta tärkeää liiketoimintaa. Viimeiselle kolmannekselle maatilatalous ei ole tärkeä tulonlähde, mutta tilojen peltoja viljellään ja siitä saadaan jossain määrin tuloa. Maantieteellisesti intensiivinen, keskimääräistä suurempien tilojen viljely keskittyy läntiseen ja eteläiseen Suomeen, jossa maatilatalouden harjoittaminen on muuta maata suotuisampaa. Kaikki kolme edellä mainittua maatilatyyppiä ovat erittäin tärkeitä maatalouden maankäytön sekä monivaikutteisuuden näkökulmasta. Suurten tilayksikköjen intensiivinen, yksipuolinen viljely johtaa biologisen ja maisemallisen monimuotoisuuden vähenemiseen. Monialaiset maatilat ovat hyvin tärkeitä, koska ne säilyttävät pellot viljeltyinä, luovat muuta taloudellista toimeliaisuutta ja siten estävät sekä ekologista että sosio-ekonomista köyhtymistä. Kolmantena ryhmänä "harrastelijaviljelijät" ovat keskeisiä maatalouden monivaikutteisuuden sekä maaseudun taloudellisen dynamiikan näkökulmasta. Tutkimuksen keskeiset johtopäätökset ovat seuraavat: 1. Noin 10 % Suomen maatalousmaasta on marginalisoitunut tai marginalisoitumis-uhan alla, suurimmaksi osaksi Itä- ja Pohjois-Suomessa. 2. Noin 10 %:a maatiloista uhkaa marginalisoituminen. 3. Keskimääräistä pienemmillä maatiloilla, joiden viljelijät ovat keskimääräistä vanhempia, marginalisoitumisvaara on suurin. 4. Voimakas maitotilojen alueellinen keskittyminen tietyille alueille ja viljan viljelyn keskittyminen tietyille alueille on suurin uhka maaperän laadulle, luonnon monimuotoisuudella ja maisemalle. 5. Monivaikutteinen maankäyttö nähdään keskeisenä mahdollisuutena välttää maa-talousmaan ja maaseutualueiden marginalisoitumista harvaan asutuilla, EU:n pohjoisilla alueilla. Nykyinen EU:n maatalouspolitiikka syrjii maatalouden harjoittamisen kannalta epäsuotuisimpia alueita, joihin koko Suomi sekä erityisesti sen itäiset ja pohjoiset alueet kuuluvat. Maatilojen yhä yksipuolisempi ja intensiivisempi tuotantotapa heikentää maaperän laatua, vähentää biodiversiteettiä ja yksipuolistaa maaseutumaisemia. Nykyiset politiikkatoimenpiteet eivät pysty pysäyttämään tätä kielteistä kehitystä. Tarvitaan uudenlaisia ja vahvempia, maatalouden ja maankäytön kestävyyttä ja monivaikutteisuutta tukevia politiikkatoimen-piteitä sekä ylipäätään keskustelua siitä, onko tällainen marginalisoitumiskehitys hyväksyttävää vai ei. Yhden ratkaisun alueiden syrjäytymisen estämiseksi tarjoavat paikalliset, ruohonjuuritasolta ylöspäin lähtevät maaseudun kehittämistoimenpiteet, jotka ovat Suomessa jo osoittautuneet vahvoiksi sosio-ekonomisen syrjäytymisen estäjiksi luoden alueelle erityisesti sosiaalista pääomaa sekä paikallistaloudellista dynamiikkaa.

The Finnish farming sector is in a process of changing and being divided into clearly identifiable types with different consequences for marginalisation. Roughly, Finnish farms can be divided into three categories. One third of the farms develop intensively their farm business by investing and enlarging their farms. Another third has other business activities in addition to farming which are important to the household economy. For the last third, farming is not an important source of income, but fields are cultivated and give some income. The rationale for continuing farming is, however, related more to multifunctional properties of farming than to economic gain. Geographically, intensive cultivation and traditionally most remunerative milk production are concentrating to the western and southern Finland. Naturally, eastern and northern Finland are mostly not suited for large farms, because it is not possible to establish large field units due to rugged terrain. All those three types of farms are very important for agricultural land use and the production of multifunctional services. Large units are often problematic because of highly intensive monocultural farming systems which lack biological and landscape diversity. Pluriactive farms are very important since they maintain fields in diversified cultivation, create other economic activities and, thus, counteract both ecological and socio-economic marginalisation. The third group of "hobby" farmers is very important to the multifunctional services of agriculture and also to the maintenance of economic dynamism. A study by Perttu Pyykkönen (2001) confirms these conclusions of regional marginalisation processes. He analysed the amount of marginal agricultural land in Finland. The research was done by studying all the farms where the farmer retired during 1996-1999. It shows the percentage of agricultural land that came up for lease or for sale and no one was interested in having. Based on his analysis, Pyykkönen concluded that 10% of all Finnish agricultural land is marginal land, and it is mainly located in eastern and northern Finland but also elsewhere in the country there are remote fields that no one is ready to cultivate. The main conclusions of the Finnish study are: 1. About 10% of agricultural land is marginalised or under the threat of marginalisation mostly in eastern and northern Finland. 2. About 10% of the farms are threatened by marginalisation. 3. Elderly farmers with smaller than average farms are most likely to be marginalised. 4. Heavy regional concentration of dairy farming in some areas and arable farming in other areas is the greatest threat to soil quality, biodiversity and landscape. 5. Multifunctional land use is seen as one potential key tool to avoid the marginalisation of agricultural land and the marginalisation of rural areas in the sparsely populated, northern parts of the European Union (EU). Based on a case study of Mäntyharju, a municipality in the region of Etelä-Savo in eastern Finland, a potentially serious marginalisation phenomenon was identified. Under the current agricultural policy regime, only very few farms can be viable in Mäntyharju, and these would mainly be dairy farms. However, when there are fewer and fewer dairy farms in remote regions in Finland, the cost of collecting the milk will grow, and under severe competition in the EU market, this may lead to the situation where the farmer has to pay for the transportation costs, while it is at the moment carried by the dairy and added to the price of milk. Without specific measures in this case, dairy farmers in most parts of Finland will be under threat. Another question is what will happen to this area if and when the dairy quotas will be removed. Most probably the production will shift to more favourable areas in Finland, and later to more southern member states of the EU. Another severe development trend is the simplification of agricultural production with all its impacts on soil quality, landscape and biodiversity and on the attractiveness of the countryside. The present policy measures do not take enough into account the problems of the northern location and the difficulties and costs of scale enlargement in a big, but sparsely populated country like Finland. The policy-enhanced concentration process of production, both to fewer farms and in fewer, in all respects more prosperous regions, counteracts all efforts at balanced territorial development and cohesion. In the case of Finland, and Mäntyharju in particular, we have to underline the fact that most of the subsidies farmers get are either LFA, environmental measures or national support based on specific geographic difficulties. The rationale behind these measures is connected to regional balance and multifunctionality. However, they seem not to be able to combat the marginalisation process. The case of Finland is somewhat hopeless in the sense that however maximal the use of agri-environmental measures, for example, is undertaken - as these measures are actually used more as substitutes of income aid - they are designed in a way which hinders their potential to attack marginalisation. For example, funds directed at the management of traditional agricultural landscapes should be available to every farm regardless of size, type of production, or the age of the farmer, and even to those landowners who are not farmers. It would also be important to find ways to stop the decline in livestock farming and even to facilitate restarting it in particular in southern Finland, but under the current development trend this is not probable. The division of farming sector into farms with different types of survival strategies should form the basis of strategy and policy measures. The first thing is to confirm the legitimacy and value of different strategic choices. The policy measures should be tailored to strengthen the economic ecological sustainability of various strategic choices. This means modifications in good agricultural practice and having ecologically sustainable supporting environmental measures. This would make the environmental support remunerative for the ecological services of public good nature provided by the farms. Also this means an emphasis on diversification measures. Pluriactivity as a development strategy for farms must be supported by suitable development measures, paying special attention to the development of human and social capital. At the same time, it is important to continue bottom-up development efforts of local rural areas to create local development dynamics. The good experiences of LEADER-type activities should guide policy formation in the future. The Finnish experience of mainstreamed local action groups (LAGs) covering the whole country is very convincing. As a counterforce towards marginalisation the evidence is strong. The high level of social capital which has been developed in the local action groups and village associations must be secured by continuing the support for these activities. The new programme period starting in 2007 should safeguard opportunities for this and try to offer more sophisticated tools in order to integrate the development efforts on the local economy to those of the civil society. Even though Finland is among the leading member states in mainstreaming LEADER-type activities, the connection to general local and regional development could be one of the new focuses. As a further policy recommendation, we suggest that the EU faces seriously the fact that its current agricultural policy marginalises naturally handicapped areas located far from the centre of the main consumer market in Europe. It is a matter of choice whether there should be any agriculture in these areas in the future. From the narrow efficiency point of view, this is, perhaps, not the case. But there should be a clear democratic political decision taken as to the future of agriculture in these areas. This is important both from the point of view of the national economy (public money could be spent elsewhere) and of the private economy, because at the moment the local people take a huge risk when they invest in their farms completely dependent on political support, and have to live under great uncertainty. On the policy measure level, this refers to the need of understanding that scale enlargement and concentration is not, in all circumstances, the key to success. If there is clear political will that agriculture should be possible also in the future in all areas in the union, areas like Mäntyharju should be allowed to tailor their farming in such a way that the old pluriactive tradition, where people used to combine scarce resources from a large physical area, could continue and become better connected to the demand of open landscape and biodiversity. In these areas, more should be invested in creating a kind of agriculture that is tied rather to the local rural economy than to the vertical chains of global food production. Multifunctionality should be operationalised closer to those who experience it, like in the case when in Mäntyharju it was suggested that one would get paid for keeping those fields in cultivation that someone looks at, like those along the road or offering a view down to the lake. At the moment, regulations concerning public purchases, for example, make it very difficult to create any local food systems. The destiny of agriculture in the periphery of the EU is not solely in the hands of the CAP, it would require better integration of other policy sectors, including regional policy and Structural Funds. In the ESPON Project (European Spatial Planning Observation Network) 2.1.3 (2004, 22), it has been aptly stated that "it is now generally understood that a purely sectoral approach is less successful in enhancing and stabilizing the performance of a region, whether rural or urban." There is a need to safeguard valuable areas, which may represent scenic, biodiversity or ecotope values. This should be incorporated in the normal productive activities related to farming but also to other income generating activities, especially to rural tourism. Also other productive activities such as food processing from agricultural, forest and fish products could gain of the image of ecologically sustainable, clean and diverse surroundings from where the products are collected. The region of Etelä-Savo is way ahead of other areas here by systematically introducing organic production as the strategic choice for agricultural production and processing in the area.
Keywords: Ma; maaseutu; maatalous; monivaikutteisuus; marginalisoituminen; maankäyttö; rural area; agriculture; multifunctionality; land use; marginalisation